(3QSGdI GHf hOYGfs - (3GHf hOYGf , eMeO Hf Ydj Hf YHjOGddg Hf CMeO Hf UGdM Hf SdjeGf, CHh fUQ,J (B494 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI Ydi QShd Gddg bGd Ydi Hf eMeO MOKfi CHj eMeO , bGd (B: (3MOKfi CHj Ydi bGd bGd di QShd Gddg Udi Gddg Ydjg hSde (B: (3jG Ydi CcJH , bdJ (B: (3heG CcJH s
(3BNQgG (B:s
(3HjfeG QShd Gddg Udi Gddg Ydjg hSde PGJ jhe EP QCjJg VMc MJi HOJ KfGjGg , abjd (B: (3ee JVMc jG QShd Gddg s
(3GdeNWhWI YHGQI Yf CQHYjf MOjKkG eY TQMgG ai GdNWH hGdehGYXs
(3cJHJ HYV YHGQGJgG hcdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B26s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs